36 Evaluation of Compensatory Growth of 90-kg Finishing Pigs Previously Fed a Low Lysine Diet - Rao, Zhong-Xing (J Anim Sci, 2021)
A total of 346 pigs (241×600, DNA, Columbus, NE; initially 88.6 kg) were used in a 44-day trial to evaluate compensatory growth of pigs previously fed very low lysine diets. Two diets [control and corn (98% corn and 2% vitamins and minerals)] were arranged into 4 nutritional strategies. One group of pigs (control) was fed the control diet from d 0 to 44. The other three groups of pigs were fed the corn diet for 14, 21, or 28-d and then fed the control diet until day 44. The control and corn diets contained 0.70 and 0.18% standardized ileal digestible Lys, respectively. Pens were assigned to nutritional strategies in a randomized complete block design based on initial BW with 9 pens per treatment. On average, pigs fed the corn diet grew 49% slower than the control. Pigs previously fed the corn diet had 28% increased (P < 0.05) ADG during the first week of switching to the control diet and 12% faster (P < 0.05) ADG than the control for the rest of the trial. Despite this increase in ADG, final BW on d 44 was lower (P < 0.05) compared to the control for pigs fed the corn diet for 21 or 28-d. From d 0 to 44, control pigs and pigs fed the corn diet for only 14-d had increased (P < 0.05) ADG compared to pigs fed the corn diet for 21 and 28-d. Feed efficiency was decreased (P < 0.05) when the corn diet was fed and increased (P < 0.05) during the period of compensatory growth; however, overall G:F decreased (P < 0.05) as pigs were fed the corn diet longer. The data suggest that compensatory growth was observed when pigs fed the corn diet for 21 or 28-d followed by the control diet within a 6-week-period, but overall growth performance was still reduced compared to the control. [Image: see text]